Counseling in the Anthropocene: Addressing Social Justice Amid Climate Change. Issue 3 (7th July 2021) - Hilert, Alexander J.
Abstract : Scientists have increasingly called for the recognition that Earth has entered a new geological epoch called the Anthropocene. Researchers believe anthropogenic climate change and ecological degradation will have the greatest impacts on communities that are socially and economically marginalized. This article will explore the role of counselors in the Anthropocene as environmental justice advocates through the application of the Multicultural and Social Justice Counseling Competencies (Ratts et al., 2015). La comunidad científica ha insistido cada vez más en el reconocimiento de que la Tierra ha entrado en una nueva era geológica denominada Antropoceno. Los investigadores creen que el cambio climático antropogénico y la degradación ecológica tendrán un impacto máximo en las comunidades que se encuentran social y económicamente marginadas. Este artículo explora el papel de los consejeros en el Antropoceno como defensores de la justicia medioambiental a través de la aplicación de las Competencias en Consejería Multicultural y de Justicia Social (Ratts et al., 2015).